2022
DOI: 10.1177/01447394221076344
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing sense of belonging and satisfaction among online students in multi-track public affairs programs: A case analysis of immersion courses

Abstract: Many graduate public affairs programs offer both residential and online options for students. One of the challenges for multi-format programs is creating a sense of belonging among online students who may never set foot on campus. In 2017, the MPA program at the University of North Carolina at Chapel Hill developed an “immersion” course designed for residential and online students in a weekend intensive format on campus to help create a greater sense of connectedness and satisfaction among (principally) online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Adding to that, research also shows that there was a significant change in emotional involvement, largely driven by a very significant drop in students' attitude toward the learning activities (Sundarasen et al, 2020). The shift to online learning influenced students' perceptions of the class's value (Bruggeman, et al, 2022;Stephens and Morse, 2022;Brown, et al, 2021;Aristovnik et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Adding to that, research also shows that there was a significant change in emotional involvement, largely driven by a very significant drop in students' attitude toward the learning activities (Sundarasen et al, 2020). The shift to online learning influenced students' perceptions of the class's value (Bruggeman, et al, 2022;Stephens and Morse, 2022;Brown, et al, 2021;Aristovnik et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Research by Thomas et al (2014) indicated that "staff and students expressed greater satisfaction with online courses that successfully fostered a sense of belonging among students" (p. 76). A sense of belonging influences a person's emotional and cognitive patterns and is considered key to improving academic motivation, (social) integration, satisfaction (Stephens & Morse, 2022), achievement (Pedler et al, 2021) and retention rates (Peacock et al, 2020). Strayhorn (2018) found that graduate students thrived and excelled "where they feel like they belong" (Strayhorn, 2018, p. 138).…”
Section: Introductionmentioning
confidence: 99%